Deciphering the therapeutic potential of trimetazidine in rheumatoid arthritis via targeting mi-RNA128a, TLR4 signaling pathway, and adenosine-induced FADD-microvesicular shedding: In vivo and in silico study - Enas Omran; Abdullah R. Alzahrani; Samar F. Ezzat; Ghada Ellithy; Marwa Tarek; Eman Khairy; Eman Khairy; Mohamed M. Ghit; Ahmed Elgeushy; Tahani Mohamed Ibrahim Al-Hazani; Ibrahim Abdel Aziz Ibrahim; Alaa Hisham Falemban; et al. (Frontiers Media S.A., 2024)
Rheumatoid arthritis (RA) is a debilitating autoimmune condition characterized by chronic synovitis, joint damage, and inflammation, leading to impaired joint functionality. Existing RA treatments, although effective to some extent, are not without side effects, prompting a search for more potent therapies. Recent research has revealed the critical role of FAS-associated death domain protein (FADD) microvesicular shedding in RA pathogenesis, expanding its scope beyond apoptosis to include inflammatory and immune pathways. This study aimed to investigate the intricate relationship between mi-RNA 128a, autoimmune and inflammatory pathways, and adenosine levels in modulating FADD expression and microvesicular shedding in a Freund's complete adjuvant (FCA) induced RA rat model and further explore the antirheumatoid potency of trimetazidine (TMZ). The FCA treated model exhibited significantly elevated levels of serum fibrogenic, inflammatory, immunological and rheumatological diagnostic markers, confirming successful RA induction. Our results revealed that the FCA-induced RA model showed a significant reduction in the expression of FADD in paw tissue and increased microvesicular FADD shedding in synovial fluid, which was attributed to the significant increase in the expression of the epigenetic miRNA 128a gene in addition to the downregulation of adenosine levels. These findings were further supported by the significant activation of the TLR4/MYD88 pathway and its downstream inflammatory IkB/NFB markers. Interestingly, TMZ administration significantly improved, with a potency similar to methotrexate (MTX), the deterioration effect of FCA treatment, as evidenced by a significant attenuation of fibrogenic, inflammatory, immunological, and rheumatological markers. Our investigations indicated that TMZ uniquely acted by targeting epigenetic miRNA128a expression and elevating adenosine levels in paw tissue, leading to increased expression of FADD of paw tissue and mitigated FADD microvesicular shedding in synovial fluid. Furthermore, the group treated with TMZ showed significant downregulation of TLR4/MYD88 and their downstream TRAF6, IRAK and NF-kB. Together, our study unveils the significant potential of TMZ as an antirheumatoid candidate, offering anti-inflammatory effects through various mechanisms, including modulation of the FADD-epigenetic regulator mi-RNA 128a, adenosine levels, and the TLR4 signaling pathway in joint tissue, but also attenuation of FADD microvesicular shedding in synovial fluid. These findings further highlight the synergistic administration of TMZ and MTX as a potential approach to reduce adverse effects of MTX while improving therapeutic efficacy.